Development of the national policy in the field of career guidance as a tool for the development of the welfare state (Хабаршы. Психология және социология сериясы, 2025)
The relevance of this scientific study lies in the growing significance of analyzing state-level strategies in the sphere of vocational guidance as a critical factor contributing to the formation and development of the welfare state. In contemporary socio-political discourse, the role of professional orientation has shifted from a narrow educational task to a broader instrument of socio-economic regulation and social integration. Accordingly, this research seeks to explore the interconnection between state-led career guidance policies and the structural evolution of the welfare state. The central objective is to evaluate the extent to which national policies in vocational guidance contribute to enhancing social development indicators and consolidating welfare institutions.The study sets out a series of research tasks to achieve this aim. These include: the theoretical and methodological analysis of the state's role in career guidance as a developmental mechanism; the identification of global trends in public policy on youth career assistance; a comparative assessment of international best practices in implementing vocational orientation strategies; the development of methodological tools to evaluate the impact of diverse state approaches on welfare development; and the formulation of policy recommendations for public administration bodies regarding the use of career guidance as a strategic tool for social state advancement.The research is grounded in a systems analysis approach, allowing the examination of vocational guidance as part of a complex and interrelated system operating under conditions of political and economic uncertainty. A comprehensive set of qualitative and quantitative research methods was employed, including comparative analysis, logical reasoning, synthesis, deduction, classification techniques, and sociological surveys. The empirical part of the study is supported by visualized data in the form of tables and charts, which illustrate the characteristics and effectiveness of various state approaches, stages of career guidance implementation, structural models of vocational education institutions, and the results of surveys conducted among target populations.Keywords: methods of improving the state activity, sustainable social development, shortage of personnel, vocational guidance of applicants.